ANALISIS METODE SEM UNTUK KURIKULUM SMP RSBI/SBI DENGAN STANDAR KURIKULUM NASIONAL - Sudjono, Hary; Choiri, Moch.; Astuti, Murti; Oktavianty, Oke; Dewi, Galuh Ratna; Andari, Susi Novi (INTEKNA informasi teknik dan niaga, 2013)
Currently there are a lot of junior SBI / RSBI in East Java province and to increase the quantity in each year. Changes and additions to the curriculum a better curriculum is the government's efforts in developing the educational level in particular junior level in In-donesia. Curriculum SBI is known for referring to international standards commonly used by developing countries. Completeness of infrastructure and professional competencies possessed by the teacher / lecturer can be measured by the success of SBI curriculum developed by the government. So far, research on school SBI / RSBI have been carried out. The study was made to determine the relevance (effectiveness and suitability) SBI curriculum with the national curriculum, which will be able to know the relationship between them. On the other hand, the professional competence of the teacher / lecturer also test them to determine whether there is a relationship with SBI curriculum currently implemented.